2020
DOI: 10.4315/0362-028x.jfp-19-288
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Histamine in Canned Fish Samples (Tuna, Sardine, Kilka, and Mackerel) from Markets in Tehran

Abstract: Food poisoning is one of the most addressed health issues and has raised notable concerns. Histamine is the biogenic amine responsible for scombroid poisoning, which is due to the histidine decarboxylation by bacterial decarboxylases in various types of fish and fish products. The present investigation was conducted to measure the concentration of histamine in canned fish samples of tuna in oil (n = 18), tuna in oil with vegetables (n = 15), tuna in brine (n = 9), kilka in oil (n = 9), sardine in oil (n = 3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The limit of detection, and often above 500 ppm in illness-causing fish have been reported due to fish consumption (13). According to the codex guidelines, the maximum allowable limit of histamine concentration is 200 mg kg -1 , while the INS has established this limit below 100 mg kg -1 (7). study showed that 46.6% of the samples contained histamine and 18.3% of the samples exceeded the FDA limit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit of detection, and often above 500 ppm in illness-causing fish have been reported due to fish consumption (13). According to the codex guidelines, the maximum allowable limit of histamine concentration is 200 mg kg -1 , while the INS has established this limit below 100 mg kg -1 (7). study showed that 46.6% of the samples contained histamine and 18.3% of the samples exceeded the FDA limit.…”
Section: Resultsmentioning
confidence: 99%
“…The most common biogenic amines include histamine, putrescine, tyramine, cadaverine, and phenylethylamine, which originates from the decarboxylation of histidine, ornithine, tyrosine, lysine, and phenylalanine, respectively (5)(6)(7). Histamine [1Himidazole-4-ethanamine], is a potentially hazardous compound and has historically been a major cause of Scombroid fish poisoning (8).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coefficient, recovery percentage, RSD for repeatability, limit of detection, and limit of quantification were 0.99, 82%, 1.3%, 1.5 mg/kg, and 5 mg/kg, respectively, which actually confirmed the feasibility of this method to detect histamine. A significantly different histamine concentration was found between canned tuna in oil and canned tuna in brine (85). HPLC with single wavelength UV detection is not fully appropriate for the unequivocal identification of histamine in these samples.…”
Section: Analytical Chemistry-based Techniquesmentioning
confidence: 89%
“…The influences of prenatal canned fish on cord blood biomarkers remain largely uninvestigated. Canned fish is high in histamine 13 . Histamine not only triggers oxidative stress 31 but also promote chemotaxis of eosinophils and neutrophils 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Some have found fish to protect against, whereas others found it to predispose to, childhood allergic diseases 5 , 9 11 . Meanwhile, processed fish, such as fried fish sticks 12 and canned fish 13 , have been demonstrated to contain pro-oxidants but rarely studied in the prenatal period. Whether the intake of various types of fish, including potential sources of antioxidants or oxidants, alters cord blood total IgE (cIgE) levels, a well-known predictor of childhood allergy 14 , remains unclear.…”
Section: Introductionmentioning
confidence: 99%